FEMINISASI KEMISKINAN DI DESA PRAMBON - Firda Kristianah; Ilmi Usrotin Choiriyah (FISIP UWP, 2020)
The feminization of poverty which has the meaning of women's poverty is the cause of the government to take action in the form of a program of combining Poverty Mitigation Mitigation. This program is one of the instruments of control that is expected in its implementation to actually be able to actually solve the problem of poverty problems based on women at the family level. Prambon Village is one of the villages that has households with female head of households (KRTP) with a welfare level of 10 Lowest% (Decile 1). This research was conducted with the aim of analyzing and describing the conditions of feminization of poverty in the village of Prambon. The method used is a qualitative method with data collection which is done by means of observation, interviews, and documentation. The results of this study indicate that there are 3 types of feminization of poverty experienced by female household heads who receive assistance in the Palin Matrix Mitigation Mitigation Program in Prambon Village which includes 3 female household heads due to divorce, 1 female household head with husband's disability, and 16 female household heads with husband's death condition.